ChemInform Abstract: Broensted Acid Promoted One‐Pot Synthesis of 4‐Aryl‐3, 4‐dihydrocoumarins. Issue 43 (7th October 2016) - Chen, Cheng; Zhang, Rui; Lin, Long; Yang, Guang‐Fu; Wu, Qiong‐You
Abstract: A mild and facile approach to the title compounds, which are of interest in natural product and medicinal chemistry, becomes optimal in the presence of HClO4 .